Literacy for Work: Exploring Dominant Discourses about Work and Literacy in the Everyday Practice of Adult Literacy Education - Jennifer A. Sandlin (Adult Education Research Conference, 2000)
This paper first discusses the move in adult literacy policy to link literacy education to workforce development. It then argues that literacy researchers need to examine how dominant discourses about education and work are enacted in the everyday practices of adult literacy classrooms.